Two different copper sites in hexakis(1-methyltetrazole)copper(II) bis(tetrafluoroborate) - Wijnands, P.E.M.; Maaskant, W.J.A.; Reedijk, J. (Chemical physics letters, 1986)
An electron spin resonance study at temperatures between 300 and 4 K demonstrates that the two crystallographically inequivalent Cu(II) sites in the title compound are subject to different Jahn-Teller behaviour. It is shown that this is not induced by cooperative interactions between the Jahn-Teller sites but arises from the different lattice symmetries of the two sites.